Histolopathological exploration & Morphological changes of thyroid gland with Grave disease - Layla Alhasan (University of Thi-Qar Journal, 2019)
This study aimed to explain the signification of histological features and determined the morphological changes of Grave disease. The study includes (8) normal as control group and (10) abnormal represented group as which suspected with Grave disease of thyroid glands have been obtained from Al-Hussein teaching hospital, all cases were females. Histological exam explain comparison of normal and abnormal of thyroid with that revealed dominant features which are hyperplasia in epithelial cell of follicular, highly infiltration of lymphocyte, irregular shape of large and medium follicles and formation of papillae within these follicles. Also colloid materials appeared pale in color and unfiltered to stroma of lobe due to the degeneration which occurred in epithelial cell of follicles. In addition, the study determined the morphological parameters of normal and Graves disease which involved diameter of follicles and epithelial cells heights measurements as well as the parameters attained 252,120,10;650,420,70 respectively 20,10,10;60,40,10 respectively. The study reported that there is a high significant differences between diameter of large and medium follicles measurement in control group in compare with.Grave disease group where as there is no significant difference between diameter of small follicles in control group and Graves disease group as well as the study provided the same significant differences for epithelial cells height of follicles. The study it is concluded that Grave disease associated with a histopathlogical in different degrees among patient.